Synthesis, an Experimental and Quantum Chemical Computational Study: Proton Sharing in 4-Morpholinium Bis(Hydrogen Squarate) - Korkmaz, U.; Topcu, Y.; Taş, M.; Bulut, A. (Elsevier, 2015)
The experimental and theoretical investigation results of a novel organic squarate salt of 4-Morpholinium bis(hydrogen squarate) (1), C6H 14ON+·C8H3O8-, were reported in this study. The crystal structure of the title compound was found to crystallize in the triclinic P - 1 space group. In the crystals of 1 the morpholine ring adopts the chair conformation with the ethyl group in the equatorial and hydrogen atoms in axial positions. The hydrogen squarate anions are linked into a homoconjugated anion, [(HSQ)2H], by a short symmetric, nonlinear O8⋯H2⋯O2 hydrogen bond of 2.444 (2) Å. The structural and vibrational properties of the compound were also studied by computational methods of ab-initio performed on the compound at DFT/B3LYP/6-31++G(d,p) (2) and HF/6-31++G(d,p) (3) level of theory. The obtained calculation results on the basis of two models for both the optimized molecular structure and vibrational properties for the 1 obtained are presented and compared with the X-ray analysis result. On the other hand the molecular electrostatic potential (MEP), electronic absorption spectra, frontier molecular orbitals (FMOs), conformational flexibility and non-linear optical properties (NLO) of the title compound were also studied at the 2 level and the results are reported. In order to evaluate the suitability for NLO applications thermal analysis (TG, DTA and DTG) data of 1 were also obtained. © 2014 Elsevier B.V. All rights reserved.
Keywords: Quantum Chemical Calculations; Squaric Acid; Strong Hydrogen Bonding; Vibrational Spectra; X-Ray Diffraction